THE ROLE OF WOMEN IN THE TEACHING-RESEARCH IN TURKEY - Nihal Apaydin (Asociación Argentina de Anatomía Clínica, 2023)
There are 131 government, 75 private Universities in Türkiye. A demographic data on the number of women working as academic stuff in these Universites is missing and needs to be evaluated. However, the data related to Ankara University Faculty of Medicine show that on the number of female administrators and representatives in academic and administrative fields is higher than that of men.